2011
DOI: 10.3233/jad-2011-091402
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Neuropathology: The MRC Cognitive Function and Aging Study Experience

Abstract: We here describe the study-design major findings from the neuropathological component of the Medical Research Council Cognitive Function and Aging Study (MRC CFAS). MRC CFAS is a population-representative study of aging and health including more than 18000 participants at baseline. More than 500 brain donations were accrued to date and have been subjected to comprehensive pathological assessment. This resource enables a thorough epidemiological description of the neuropathology associated with dementia in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 68 publications
5
77
2
1
Order By: Relevance
“…29 Community-based pathological studies, including the Honolulu-Asia Aging Study and MRC Cognitive Function and Aging Study, found CAA to be associated with cognition even after controlling for age and neurodegenerative pathology. 28,30 The Religious Orders Study showed that moderate-to-severe CAA was linked to impairment in specific cognitive domains, particularly perceptual speed, assessed with the Symbol Digit Modalities Tests and Number Comparison tests 31 ; however, we found no association between CMBs and speed and attention functions, also assessed by the Symbol Digit Modalities test. Possible explanations include the following: first, our patients all attended hospital with ischemic stroke or TIA, whereas the Religious Orders Study included community-based subjects, in whom only 36% had cerebral infarction at autopsy; and second, the Religious Orders Study found associations with moderate-to-severe CAA pathology, whereas our patients with strictly lobar CMBs probably have less severe CAA pathology.…”
Section: May 2013contrasting
confidence: 52%
“…29 Community-based pathological studies, including the Honolulu-Asia Aging Study and MRC Cognitive Function and Aging Study, found CAA to be associated with cognition even after controlling for age and neurodegenerative pathology. 28,30 The Religious Orders Study showed that moderate-to-severe CAA was linked to impairment in specific cognitive domains, particularly perceptual speed, assessed with the Symbol Digit Modalities Tests and Number Comparison tests 31 ; however, we found no association between CMBs and speed and attention functions, also assessed by the Symbol Digit Modalities test. Possible explanations include the following: first, our patients all attended hospital with ischemic stroke or TIA, whereas the Religious Orders Study included community-based subjects, in whom only 36% had cerebral infarction at autopsy; and second, the Religious Orders Study found associations with moderate-to-severe CAA pathology, whereas our patients with strictly lobar CMBs probably have less severe CAA pathology.…”
Section: May 2013contrasting
confidence: 52%
“…The study details have been described in detail elsewhere [11][12][13][14]. Assessment of dementia in the study was based on a standardised assessment for psychiatric disorders in older people (GMS AGECAT).…”
Section: Tissue and Casesmentioning
confidence: 99%
“…Population-based autopsy studies show that brain infarctions and severe intracranial atherosclerosis increase the odds of dementia independent of AD pathologies [109][110][111][112], suggesting that intracranial atherosclerosis and microvascular pathologies play a part in the development of the dementia syndrome. Indeed, intracranial atherosclerosis and AD may share common pathogenic mechanisms, such as oxidative stress, inflammation and toxic b-amyloid.…”
Section: Cerebral Small-vessel Diseasementioning
confidence: 98%